Ледяной поцелуй: повесть / И. Молчанова - Молчанова Ирина (Лекарство от грусти, 2014)
Экземпляры: ф.19 (20151225) / Инвентарный номер: 525231 / Цена: 153.00. / Сис.шифр: Р2 / Авт.знак: М 76 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-4